Heaviness in Metal Music Production, Volume II : Learn From the Masters - Jan-Peter Herbst; Mark Mynett (Focal Press, 2026)
Heaviness in Metal Music Production, Volume II: Learn from the Masters details how the fundamental musical quality of metal, ‘heaviness', is created during record production, offering unprecedented learning opportunities provided by eight world-leading producers mixing the same multi-track of the song ‘In Solitude'and sharing insights into their creative visions and technical realizations.The book contains unabridged interviews with the producers about their conceptual understandings of heaviness and approaches to engineering ‘In Solitude', enriched by nearly 300 illustrations of their sound engineering techniques. Beginning with a summary of the researchers'main findings on how heaviness is defined, the study then moves on to a comparative analysis of the producers'mixes, providing structured guidelines for critical listening. These interviews and mix documentations are complemented by contextual information about heaviness in metal music production, covering non-musical, associative factors that influence what is possibly the most valued feature of metal music—heaviness.Heaviness in Metal Music Production will appeal to students of metal music, music technology and production, ethnomusicology, cultural studies, media, and communication. It will also serve as a practical primer for professional musicians, recording engineers, and producers to improve their own production values or to allow for experimentation with new approaches.This two-volume set offers a well-rounded insight into the production of heaviness in theory and practice.The Open Access version of this book, available at www.taylorfrancis. com, has been made available under a Creative Commons Attribution (CC-BY) 4.0 International license.